(untitled) (Journal of the College of Basic Education, 2022)
Steganography is known as the art and technique of text messages concealed in such a manner that one apart from the meant recipient defines the message presence. Because of this reason it has become almost essential to conserve the systems free from various internet attacks and take occupy steps to remove any danger. Linguistic steganography, a kind of steganography is famous as a set of techniques and manners that allow the hiding of any digital data inside scripts based on some linguistic knowledge. Linguistic steganography is of various shapes and has varied applications. This research offers in a new method to use two levels to hide, the first level hides by embedding and addition but the second level hides by injection. The first level embeds a secret message one bit in the LSB in the FFT with the addition of one kashida. Using DRLR is RNG to find position to hide within the text. The second level is the injection of random single or double quotation within the text. This paper presents a linguistic steganography for scripts written in Arabic language, using kashida and Fast Fourier Transform on the basis of using new technique entitled Dynamic Random Linear Regression as location to hide secret message. The proposed approach is an attempt to present a transform linguistic steganography using levels for hiding to improve implementation of kashida, and improve the security of the secret message by using Dynamic Random Linear Regression. This method is tested in terms of security and capacity, transparency, and robustness and this is way better than previous methods. The proposed algorithm has ideal steganographyic properties.